A new species of Bothriodontinae, Merycopotamus Thachangensis (Cetartiodactyla, Anthracotheriidae) from the late Miocene of Nakhon Ratchasima, northeastern Thailand - Rattanaphorn Hanta (2018)
Merycopotamus thachangensis, sp. nov. (Cetartiodactyla, Anthracotheriidae, Bothriodontinae) was discovered from a mined sand pit in Tha Chang village in Nakhon Ratchasima Province, northeastern Thailand. The specimen is a nearly complete cranium with left P3-M3 and right M1-M3. It is the first known Merycopotamus in Thailand. The new species has a nearly divided mesostyle with a remnant at the base. No small crest is developed from the buccal style on upper molars. The postparacrista and premetacrista are parallel, pointing buccally to distobuccally. The major palatine foramen is positioned at P2-P3. The naso-frontal suture is lobe-like. There is a single supraorbital foramen with a distinct groove. There is no contact between the nasal and lacrimal bones. M. thachangensis shows a mixture of derived and primitive features that distinguish it from the previously known species of Merycopotamus. The new Thai species might have evolved from M. medioximus in the early late Miocene of Siwaliks, though the retention of and/or secondary reversal to primitive character states in M. thachangensis makes it difficult to determine the phylogenctic relationships of the new species to the other Merycopotamus species. Although the provenance of other mammalian fossils from the Tha Chang area is problematic, our analyses have indicated that they can be sorted into three fossil assemblages of middle Miocene, late Miocene and early Pleistocene age. M. thachangensis is most likely late Miocene in age, possibly late late Miocene. © 2008 by the Society of Vertebrate Paleontology.